Pengaruh Senam Kaki Terhadap Nilai Ankle Brachial Index (Abi) Pada Pasien DM Tipe II Di Persadia Unit Dr. Moewardi Tahun 2015 - Agus Trianto; Rini Tri Hastuti (Poltekkes Kemenkes Surakarta, 2017)
Abstract : Kind II of DM, Foot Excercise, Ankle Brachial Index (ABI) Value. Many Patients that go through complications of Type II DM. One of the complication is foot diabetik, its needed implementation to prevent of the complication. The implementation that be doing is exercise. Exercise that be doing is foot exercise that have function to increase the peripheral blood circulation. The Objective of the research is to know the effect of foot exercise to Ankle Brachial Index (ABI) value of the type II of DM patient in unit of Persadia Dr. Moewardi hospital year 2015.Kind of the research is quasy experimental research. Design of the research is one group pretest post test design. The researcher conducted measurement value Ankle brachial index (ABI) before doing foot exercise and measurement Ankle Brachial Index (ABI) value after foot exercise. The analysis by using pairet test t-test. Result of the research from paired t-test, the effect of foot exercise showed findings Sig value. (2-tailed) is 0,001 or ABI value p <0.05, with average change ABI value before and after is equal to 0.05211, So from the test result of paired t-test it can be meant that Ho is rejected and Ha be accepted. That have meaning there are effect of foot exercise to ABI value.